Pengaruh Ukuran Partikel Arang Sekam Padi Dan Waktu Refluks terhadap Kadar Abudan Daya Serap Karbon Sekam Padi - Solihudin, Solihudin; Noviyanti, Atiek Rostika; Rahayu, Iman (Jurnal Natur Indonesia, 2016)
The highest content in rice husk is ash with its main component of silica. Silica in ash causes the low adsorption capacity. Activated carbon from rice husk can be obtained by lowering the ash content. The aim of this study is determine the effect of particle size of charcoal and reflux time the ash content using a solution of potassium carbonate. The activation of rice husk char was carried out by using reflux methods with a potassium carbonate solution. The resulted carbon was washed using hydrochloric acid tested using iodine and methylene blue to examine of its adsorbance. The particle size of rice husk and reflux time decrease ash content in rice husk. In general, husk with the size of 80 mesh can produce carbon with low ash content and high absorption using reflux time at least for 120 minutes. Rice husk size of 100 mesh refluxing with potassium carbonate for 150 minutes can reduce the ash content as 91.85% and adsorptivity of the iodine at 331 mg.g -1 .